IMPACT OF STUDENT TEAMS ACHIEVEMENT DIVISION BASED ON HYBRID LEARNING AND JIGSAW TOWARD HIGH ORDER THINKING SKILL VOCATIONAL HIGH SCHOOL - Kurniawan, Sandi; Sutadji, Eddy; Sudjono, Imam (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The background of the research is the low assessment of high order thinking skills of students due to the conventional methods used by the school. The aims of this study are: (1) how student learning activities when using hybrid learning Student Teams Achievement Division (STAD) and jigsaw, (2) how student learning activities when taught using the direct learning model, and (3) the effect of hybrid learning Student Teams Achievement Division (STAD) and jigsaw towards high order thinking skills. This study used a quasi experimental nonequivalent control group design with the sample of 50 students from a population of vocational high school students in Ponorogo. Data collection techniques used instruments in the form of high order tests and non-test instruments in the form of observation sheets. Data analysis used was independent sample t-test. The results showed: (1) the use of Student Teams Achievement Division (STAD) based on hybrid learning and jigsaw made 28% of students were very active, 28% of students active, and 44% of students quite active in the learning process, this was evidenced by an average value of 70.56, (2) the use of direct learning models in learning made 24% of students quite active, 36% of students less active, and 40% of students passive in the learning process, which can be seen from the acquisition of an average value of 51.52, and (3) there was a significant effect of Student Learning Achievement Division (STAD) based on hybrid learning and jigsaw on students' high order thinking skills.